Conductivity, Dielectric Loss, and Electrical Heterogeneous Microstructure of Eight‐Layer Twinned Hexagonal Perovskite Ceramics Ba8CuTa6O24−δ. Issue 8 (19th April 2013) - Yu, Xiaodi; Chai, Shiqiang; Kuang, Xiaojun; Su, Congxue; Pan, Fengjuan; Fang, Liang; Su, Qiang; Davies, P. K.
<x xml:space="preserve">Abstract</x> Ba8CuTa6O24−δ ceramics possess exceptionally high microwave dielectric loss among the eight‐layer twinned hexagonal perovskite Ba8MTa6O24 (M = Zn, Co, Ni, Mg, Cu) analogs. Impedance spectroscopy measurement demonstrates that the eight‐layer Ba8CuTa6O24−δ ceramics show the electrical heterogeneous microstructure, consisting of leaky insulating grains and more resistive grain boundary regions. This induced internal barrier layer capacitance (IBLC) effects on Ba8CuTa6O24−δ ceramics. The heterogeneous electrical microstructure is associated with partial reduction of Cu2+ to Cu+ and oxygen loss during the sintering procedure and limited reoxidization along grain boundary regions on cooling. The existence of Cu+ in Ba8CuTa6O24−δ ceramic is confirmed by X‐ray photoelectron spectroscopy measurement. The leaky insulating bulk property for the Ba8CuTa6O24−δ ceramics is compared with the highly insulating bulk behavior of other low dielectric loss analogs, which indicates that the significant defects of Cu+ and oxygen vacancies are responsible for the high microwave dielectric loss of the Ba8CuTa6O24−δ ceramics.